The Role of the Regulator Fur in Gene Regulation and Virulence of Riemerella anatipestifer Assessed Using an Unmarked Gene Deletion System - Guo, Yunqing; Hu, Di; Guo, Jie; Li, Xiaowen; Guo, Jinyue; Wang, Xiliang; Xiao, Yuncai; Jin, Hui; Liu, Mei; Li, Zili; Bi, Dingren; Zhou, Zutao (Frontiers in Cellular and Infection Microbiology, 2017)
Riemerella anatipestifer, an avian pathogen, has resulted in enormous economic losses to the duck industry globally. Notwithstanding, little is known regarding the physiological, pathogenic and virulence mechanisms of Riemerella anatipestifer (RA) infection. However, the role of Ferric uptake regulator (Fur) in the virulence of R. anatipestifer has not, to date, been demonstrated. Using a genetic approach, unmarked gene deletion system, we evaluated the function of fur gene in the virulence of R. anatipestifer. For this purpose, we constructed a suicide vector containing pheS as a counter selectable marker for unmarked deletion of fur gene to investigate its role in the virulence. After successful transformation of the newly constructed vector, a mutant strain was characterized for genes regulated by iron and Fur using RNA-sequencing and a comparison was made between wild type and mutant strains in both iron restricted and enriched conditions. RNA-seq analysis of the mutant strain in a restricted iron environment showed the downregulation and upregulation of genes which were involved in either important metabolic pathways, transport processes, growth or cell membrane synthesis. Electrophoretic mobility shift assay was performed to identify the putative sequences recognized by Fur. The putative Fur-box sequence was 5′-GATAATGATAATCATTATC-3′. Lastly, the median lethal dose and histopathological investigations of animal tissues also illustrated mild pathological lesions produced by the mutant strain as compared to the wild type RA strain, hence showing declined virulence. Conclusively, an unmarked gene deletion system was successfully developed for RA and the role of the fur gene in virulence was explored comprehensively.